MOTIVATION AND LANGUAGE LEARNING STRATEGIES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This study explores the intricate relationship between motivation and language learning strategies (LLS). Motivation is a key affectivefactor influencing language acquisition, while strategic behavior in learning enhances learners’ autonomy and success. By reviewing empirical studies and theoretical frameworks, the paper investigates how different types of motivation affect the use and efficacy of learning strategies among language learners. Results suggest that high motivation, particularly intrinsic and integrative motivation, correlates positively with frequent and effective use of a variety of strategies.